THE EFFECT OF NARCISSIN FLAVONOID ON THE PEROXIDATION PROCESS OF HEART MITOCHONDRIA MEMBRANE LIPIDS IN EXPERIMENTAL ISCHEMIA (Conferencea, 2022)
Various experimental models of myocardial injury have shown the relationship between the accumulation of free fatty acids, the activity of intracellular phospholipases and the preservation of myocardial energy metabolism at the level of mitochondria. In conditions of ischemia, the functional activity of myocardial cells is disturbed by changes in the mitochondrial membrane. Mitochondrial membrane ion transport system disorders, including mPTP permeability increase, lead to disruption of regulation of Ca2+ ions between cytosol and matrix. As a result, the release of cytochrome c from the matrix leads to the development of apoptosis processes. In addition, as a result of the violation of myocardial contraction processes, heart contraction rhythms can be lost.